Decision-makers' logic of control and SME international performance. Issue 5 (6th October 2021) - Karami, Masoud; Tang, Jintong
Abstract : Purpose: This paper aims to investigate the mediating role of founders/managers' logic of control in transforming experiential knowledge and human capital into successful international performance of small- and medium-sized enterprises. Design/methodology/approach: Using a quantitative methodology, this study used hierarchical regression analysis to test the hypotheses. Findings: Drawing upon effectuation theory, the study proposed and found empirical evidence for the logic of control as an important mechanism that transforms experiential knowledge and human capital into international performance. Originality/value: This study contributes to the international entrepreneurship (IE) research by investigating how the application of logic of control by SME founders/managers enables them to make use of their experiential knowledge and human capital as important intangible means to achieve successful international performance. The study tested the model in New Zealand wherein SMEs play a central role in economic development and depend heavily on international markets for survival and growth.